The HSP90 inhibitor NVP‐AUY922‐AG inhibits the PI3K and IKK signalling pathways and synergizes with cytarabine in acute myeloid leukaemia cells. (29th January 2013) - Walsby, Elisabeth J.; Lazenby, Michelle; Pepper, Chris J.; Knapper, Steven; Burnett, Alan K.
Summary Heat shock protein 90 (HSP90; HSP90AA1) is a molecular chaperone involved in signalling pathways for cell proliferation, survival, and cellular adaptation. Inhibitors of HSP90 are being examined as anti‐cancer agents, but the critical molecular mechanism(s) of their activity remains unresolved. HSP90 inhibition potentially facilitates the simultaneous targeting of multiple molecules within tumour cells and represents an attractive therapeutic proposition. Here, we investigated HSP90 as a molecular target for acute myeloid leukaemia (AML) using the novel HSP90 inhibitor NVP‐AUY922‐AG. NVP‐AUY922‐AG induced dose‐dependent killing in myeloid cell lines and primary AML blasts. In primary blasts, cell death in response to NVP‐AUY922‐AG was seen at concentrations almost 2 logs lower than cytarabine (Ara‐C) (50% lethal dose = 0·12 μ mol/l ± 0·28). NVP‐AUY922‐AG was significantly less toxic to normal bone marrow (P = 0·02). In vitro response to NVP‐AUY922‐AG did not correlate with response to Ara‐C (r2 = 0·0006). NVP‐AUY922‐AG was highly synergistic with Ara‐C in cell lines and in 20/25 of the primary samples tested. NVP‐AUY922‐AG induced increases in HSP70 expression and depletion of total AKT, IKKα and IKKβ in cell lines and primary blasts. This study shows that the novel HSP90 inhibitor NVP‐AUY922‐AG has significant single agent activity in AML cells and is synergistic with Ara‐C.